DINAMIKA KONFLIK DAN RESOLUSI BERBASIS KEARIFAN LOKAL PERTAMBANGAN EMAS DI HUTAN BATANG TORU - SALMAN ALPARIS SORMIN (Jurnal Education and Development, 2019)
This study aims to determine the dynamics of conflict and resolution based on local wisdom that occurred after the operation of a gold mining company in the Batang Toru forest. The research method used to answer the problem in this study uses a qualitative research method with a descriptive analytical approach. Data analysis was performed using techniques from Miles and Huberman, namely data analysis was carried out simultaneously starting from data collection, data condensation, data display and drawing conclusions that were carried out continuously throughout the research process. Based on the results of data analysis that has been done, there are several phases of conflict that occur namely; The first phase was the disappointment with the recruitment mechanism so that the Batang Toru community held a demonstration demanding an opportunity to work for the company. Second, the environmental issue, which is the plan to dispose of mining waste from the Batang Toru River, has not been well socialized by the government or companies, causing negative perceptions both towards the government and the company. These environmental issues triggered anarchism by demonstrators because they felt they did not get accurate information about the disposal of waste into the Batang Toru River. Conflict between the Batang Toru community and PT. AR and local government are vertical conflicts caused by the failure of the communication and socialization process, resulting in a negative perception of the existence of gold mining activities in Batang Toru. Conflict resolution based on local wisdom offered as an alternative to preventing and resolving conflicts between the Batang Toru community against the company and the government, among others; optimization of Dalihan Na Tolu, revitalization of Patik, Uhum and ugari.